MEMBANGUN CLOUD COMPUTING UNTUK MANAGEMEN DATA PADA UNIVERSITAS ISLAM LAMONGAN - Agus Junaidi; Retno Wardhani; Masruroh Masruroh (Jurnal Teknika, 2018)
To improve the efficiency of work activity management at Islamic University of Lamongan requires  a  service  system  that  can  help  the  work  of  management,  especially  data  management service / file then the wake of data management services with website technology built in network of private University, website service is in the cloud Computing Local Service was built from a virtual  server  with  a  Debian  8  operating  system  and  a  server  residing  within  the  Proxmox operating system. The stages of the development of this service system include the creation of cloud services is done through several stages, namely the stage of network design, the stage of installing  the operating system Proxmox, the stage of creating a VE server in proxmox, the stage of installing  the  VE  server  with  debian8,  the  stage  of  configuring  the  VE  server  to  web  server  and  domain  Server, implementation and testing stages. And also the stages of making management services  through several stages, namely the design phase of the context diagram, the phase make usecase  service diagram, create an activity diagram, the stage of making sequence diagram, and interfaces  design stage